Genetic structure and evolutionary diversity of mating-type (MAT) loci in Hypsizygus marmoreus - Gang Wang; Yuanyuan Wang; Lianfu Chen; Hongbo Wang; Lin Guo; Xuan Zhou; Meijie Dou; Baiyu Wang; Jingxian Lin; Lei Liu; Zhengchao Wang; Youjin Deng; et al. (IMA Fungus)
Abstract The mating compatibility in fungi is generally governed by genes located within a single or two unlinked mating type (MAT) loci. Hypsizygus marmoreus is an edible mushroom in the order Agaricales with a tetrapolar system, which contains two unlinked MAT loci-homeodomain (HD) transcription factor genes and pheromone/pheromone receptor genes (P/R). In this study, we analyzed the genetic structure and diversity of MAT loci in tetrapolar system of H. marmoreus through sequencing of 54 heterokaryon and 8 homokaryon strains. Although within the HD loci, the gene order was conserved, the gene contents were variable, and the HD loci haplotypes were further classified into four types. By analyzing the structure, phylogeny, and the HD transmissibility based on the progeny of these four HD mating-type loci types, we found that they were heritable and tightly linked at the HD loci. The P/R loci genes were found to comprise three pheromone receptors, three pheromones, and two pheromone receptor-like genes. Intra- and inter-specific phylogenetic analyses of pheromone receptors revealed that the STE3 genes were divided into three groups, and we thus theorize that they diverged before speciation. Comparative analysis of the MAT regions among 73 Basidiomycete species indicated that the diversity of HD and P/R loci in Agaricales and Boletales may contribute to mating compatibility. The number of HD genes were not correlated with the tetrapolar or bipolar systems. In H. marmoreus, the expression levels of these genes at HD and P/R loci of compatible strains were found higher than in those of homonuclear/homokaryotic strains, indicating that these mating genes acted as switches for mating processes. Further collinear analysis of HD loci in interspecific species found that HD loci contains conserved recombination hotspots showing major rearrangements in Coprinopsis cinerea and Schizophyllum commune, suggesting different mechanisms for evolution of physically linked MAT loci in these groups. It seems likely that gene rearrangements are common in Agaricales fungi around HD loci. Together, our study provides insights into the genomic basis of mating compatibility in H. marmoreus.